Terminação de bovinos de corte em pastagem de capim Aruana sobressemeado com aveia e azevém associados à leguminosa e/ou adubação nitrogenada - Schmitz, Gean Rodrigo (2017)
The objective was to evaluate finishing of beef steers in Aruana pasture overseeded with oats and ryegrass and mixed with legume with or no nitrogen fertilization. The design was completely randomized, with three treatments and three replications. Three forage systems have been tested tested in winter, based on Aruana fodder (Panicum maximum, cv. Aruana) mixed with oats and ryegrass: 'Nitrogen' (N) -200 kg of N ha-1; Forage peanut and 100 kg of N ha-1; Vetch and 100 kg of N ha-1. The fertilization was shared in five applications, for 127 days. The continuous stocking system was used, with variable stocking rate, and forage on offer of 9,0 kg/100 kg of live weight. The grazing was managed with 24 castrated animals of 21 months,425 kg of initial avarage live weight. Being 18 testers and six regulators. Evaluations of forage and animal performance were made every 21 days. For animal behavior, the evaluations were done twice in each period, for 24 hours. The highest level of nitrogen fertilization showed differences in pasture structure, however, the forage daily production was similar between the treatments. The grazing time on mixture with vetch was superior for Forage peanut and similar to the others when fertilization was 200 kg of N ha-1, although, the average daily gain was similar for both treatments. The time of 20 bites and the number of steps per minute were higher for higher nitrogen fertilization, when compared to the peanut intercropping, and similar to those when mixed with vetch. Although the peanut consortium associated with 100 kg of N ha-1 caused a reduction in grazing time and presented a longer rumination time, there were no differences in the productive performance and carcass characteristics of the finished animals.